A comprehensive index for assessing regional dry-hot wind events in Huang-Huai-Hai Region, China. (April 2020) - Li, Sen; Zhang, Lei; Huang, Binxiang; He, Liang; Zhao, Junfang; Guo, Anhong
Abstract: At present, the assessment of dry-hot wind (DHW) was generally focused on the spatiotemporal characteristics of the number of DHW days, and mainly at station levels; while the evaluation methods of regional DHW events are not yet mature. In this study, daily maximum temperature, relative humidity and wind speed at 14:00 data collected from 264 meteorological stations from 1961 to 2018 was used to construct an assessment model of regional DHW events. A criterion was proposed for the determination of regional DHW events. Moreover, the duration, coverage area and daily intensity indices of regional DHW event were integrated into a comprehensive index. The criterion for the classification of the comprehensive index was determined by using the quantile method. The regional DHW events recognized in this study were consistent with the literature records, indicating that the comprehensive index can be used for regional DHW event assessment. Based on the analysis results of the comprehensive index, the annual average number of regional DHW events in Huang-Huai-Hai Region showed a decreasing trend from 1961 to 2010, and increased in 2011–2018. From 1961 to 1970, both the number of DHW events and the impacts were the largest in each decade, while the smallest DHW events number and relative light influence in 1991–2000. The event occurred from May 29–June 6, 1968, had the largest duration, coverage area and daily intensity, and the comprehensive intensity value ranked first among all events. Highlights: Evaluation index of dry-hot wind events is developed based on intensity, coverage and duration. The impacts of dry-hot wind events decreased in 1961–2000, and increased in 2001–2018. Impacts of dry-hot wind on winter wheat may increase under climate warming in China. The evaluation index provides a new way for quick assessment of dry-hot wind events.